Validation and clinical impact of novel pericoronary adipose tissue measurement on ECG-gated non-contrast chest CT. (April 2023) - Takahashi, Daigo; Fujimoto, Shinichiro; Nozaki, Yui O.; Kudo, Ayako; Kawaguchi, Yuko O.; Takamura, Kazuhisa; Hiki, Makoto; Sato, Hideyuki; Tomizawa, Nobuo; Kumamaru, Kanako K.; Aoki, Shigeki; Minamino, Tohru
Abstract: Background and aims: We aimed to develop a method for quantifying pericoronary adipose tissue (PCAT) on electrocardiogram (ECG)-gated non-contrast CT (NC-PCAT) and validate its efficacy and prognostic value. Methods: We retrospectively studied two independent cohorts. PCAT was quantified conventionally. NC-PCAT was defined as the mean CT value of epicardial fat tissue adjacent to right coronary artery ostium on ECG-gated non-contrast CT. In cohort 1 (n = 300), we evaluated the correlation of two methods and the association between NC-PCAT and CT-verified high-risk plaque (HRP). We dichotomized cohort 2 (n = 333) by the median of NC-PCAT, and assessed the prognostic value of NC-PCAT for primary endpoint (all-cause death and non-fatal myocardial infarction) by Cox regression analysis. The median duration of follow-up was 2.9 years. Results: NC-PCAT was correlated with PCAT (r = 0.68, p< 0.0001). In multivariable logistic regression analysis, high NC-PCAT (OR:1.06; 95%CI:1.03–1.10; p  = 0.0001), coronary artery calcium score (CACS) (OR:1.01 per 10 CACS increase, 95%CI:1.00–1.02; p  = 0.013), and current smoking (OR:2.58; 95%CI:1.03–6.49; p  = 0.044) were independent predictors of HRP. Among patients with CACS>0 (n = 193), NC-PCAT (OR:1.06; 95%CI:1.03–1.10; p  = 0.0002), current smoking (OR:3.02; 95%CI:1.17–7.82; p  = 0.027), and male sex (OR:2.81; 95%CI:1.06–7.48; p  = 0.028) were independent predictors of HRP, whereas CACS was not ( p  = 0.15). Multivariable Cox regression analysis revealed high NC-PCAT as an independent predictor of the primary endpoint, even after adjustment for sex and age (HR:4.3; 95%CI:1.2–15.2; p  = 0.012). Conclusions: There was a positive correlation between NC-PCAT and PCAT, with high NC-PCAT significantly associated with worse clinical outcome (independent of CACS) as well as presence of HRP. Graphical abstract: Image 1 Highlights: The CT value of non-contrast CT (NC-PCAT) is correlated with that of conventional pericoronary adipose tissue (PCAT) . High NC-PCAT value is associated with presence of high-risk plaque. NC-PCAT is a significant predictor of worse clinical outcome in coronary artery disease patients.